Novel Xanthomonas Species From the Perennial Ryegrass Seed Microbiome – Assessing the Bioprotection Activity of Non-pathogenic Relatives of Pathogens - Li, Tongda; Mann, Ross; Sawbridge, Timothy; Kaur, Jatinder; Auer, Desmond; Spangenberg, German (Frontiers in Microbiology, 2020)
The productivity of the Australian dairy industry is underpinned by pasture grasses, and importantly perennial ryegrass. The performance of these pasture grasses is supported by the fungal endophyte Epichloë spp. that has bioprotection activities, however the broader microbiome is not well characterised. In this study, we characterised a novel bioprotectant Xanthomonas species isolated from perennial ryegrass (Lolium perenne L. cv. Alto). In vitro and in planta bioassays against key fungal pathogens of grasses (Sclerotium rolfsii, Drechslera brizae and Microdochium nivale) indicated strong bioprotection activities. A complete circular chromosome of ~5.2 Mb was generated for three strains of the novel Xanthomonas sp. Based on the 16S ribosomal RNA gene, the strains were closely related to the plant pathogen Xanthomonas translucens, however comparative genomics of 22 closely related xanthomonad strains indicated that these strains were a novel species. The comparative genomics analysis also identified two unique gene clusters associated with the production of bioprotectant secondary metabolites including one associated with a novel nonribosomal peptide synthetase and another with a siderophore. The analysis also identified genes associated with an endophytic lifestyle (e.g. Type VI secretion system), while no genes associated with pathogenicity were identified (e.g. Type III secretion system and effectors). Overall, these results indicate that these strains represent a novel, bioactive, non-pathogenic species of the genus Xanthomonas. Strain GW was the designated type strain of this novel Xanthomonas sp.